Guidelines for evaluating mobile applications: A semiotic-informed approach - Nicastro, Flavio; Pereira, Roberto; Alberton, Bruna [UNESP]; Morellato, Leonor Patrícia Cerdeira [UNESP]; Baranauskas, Cecilia; Torres, Ricardo da S. (Springer Nature, 2015)
Portable devices have been experimented for data acquisition in different domains, e. g., logistics and census data acquisition. Nevertheless, their large-scale adoption depends on the development of effective applications with a careful interaction design. In this work, we revisit existing strategies for mobile application design and evaluation and use the Semiotic Ladder from Organizational Semiotics as an artifact to organize a set of guidelines. We propose a set of semiotic-informed guidelines with questions for evaluation of mobile application interfaces. We also propose a methodology for the evaluation of mobile application interfaces based on the proposed guidelines set. We demonstrate the use of the proposed methodology in the evaluation of four mobile application interfaces designed for phenological data acquisition in the field.
Keywords: Human computer interaction; Mobile application interface guidelines; Organizational Semiotics; Phenology